2013
DOI: 10.1176/appi.ps.201200574
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Management of Tobacco Dependence in Inpatient Psychiatry: Provider Practices and Patient Utilization

Abstract: Objective This investigation examined predictors of utilization of nicotine replacement therapy (NRT) during a smoke-free psychiatric hospitalization. Methods Smokers (N=324) were recruited from smoke-free adult inpatient psychiatric units. Exploratory analyses examined correlates of NRT provision and utilization. Results The prevalence of NRT use was 51% overall and was greater among patients offered NRT on admission (58%) versus later (34%), among patients with more severe depression and nicotine withdra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 12 publications
0
25
2
Order By: Relevance
“…Over the study period, 747,338 occupied bed days of care were delivered to patients. The characteristics of patients were: 57% (n=10,269) male; 60% (n=10,813) under 45 years of age; 40% (n=7180) had a primary diagnosis of schizophrenia or related disorder (ICD-10, F20-29), 20% (n=3,598) a mood disorder (F. [30][31][32][33][34][35][36][37][38][39] and the remainder other diagnoses e.g. dementia, addiction disorder; 44% (n=8,007) were formally detained under mental health legislation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the study period, 747,338 occupied bed days of care were delivered to patients. The characteristics of patients were: 57% (n=10,269) male; 60% (n=10,813) under 45 years of age; 40% (n=7180) had a primary diagnosis of schizophrenia or related disorder (ICD-10, F20-29), 20% (n=3,598) a mood disorder (F. [30][31][32][33][34][35][36][37][38][39] and the remainder other diagnoses e.g. dementia, addiction disorder; 44% (n=8,007) were formally detained under mental health legislation.…”
Section: Resultsmentioning
confidence: 99%
“…Supporting patients to temporarily abstain from smoking without the discomfort of nicotine withdrawal or encouraging a quit attempt can be achieved by promptly offering inpatient smokers NRT on admission, increasing the dose for heavily dependent smokers and education on the benefits of NRT compared to smoking tobacco. 31 Concerns about violence are impeding the introduction of smoke-free policies worldwide and such concerns may not be substantiated. Instead, adequately resourced smoke-free policies could be part of broader violence reduction strategies in psychiatric settings.…”
Section: Discussionmentioning
confidence: 99%
“…24 Predictors of NRT use posthospitalisation have not been examined. While our earlier research has demonstrated efficacy of initiating tobacco treatment during psychiatric hospitalisation, 25 the study protocol restricted NRT availability to participants intending to quit and, as a result, NRT was used by only 49% of intervention participants.…”
mentioning
confidence: 99%
“…Therefore, while existing studies indicate that menthol cigarette use is associated with increased nicotine dependence and poor smoking cessation outcomes, our findings question this pattern by raising the question of whether menthol cigarette use should remain as a commonly viewed risk factor in smoking persistence. Third, we also examined response after a standard 8 week regiment of a consistently high dose of 21 mg of the nicotine patch, which is both effective and highly utilized by treatment providers (Leyro et al, 2013; Tonnesen et al, 1999). In a large scale, time-limited nicotine replacement therapy giveaway program, menthol cigarette smokers reported greater use of any nicotine replacement therapy, but had lower quit rates (Thihalolipavan, Jung, Jasek, & Chamany, 2014).…”
Section: Discussionmentioning
confidence: 99%